Modified polyester as well as preparation method and application thereof

By synthesizing low-melting point modified polyester using specific modified monomers in polyester and effectively mixing with polyvinyl chloride and toughening agent, the problem of poor compatibility between existing low-melting point polyester and polyvinyl chloride is solved, and the high strength, toughness and cold resistance of composite materials are achieved, which is suitable for the production of sole materials.

CN119570206AActive Publication Date: 2025-03-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311138739.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-05
Publication Date
2025-03-07
Estimated Expiration
2043-09-05

AI Technical Summary

Technical Problem

The existing low-melting point polyester has poor compatibility with polyvinyl chloride, resulting in poor strength and toughness of the mixed sheets and unsatisfactory impact resistance.

Method used

By using a specific modified monomer as a comonomer of the polyester, a low melting point modified polyester is synthesized. The modified polyester not only has a low melting point, but can be effectively kneaded with the toughening agent to avoid degradation of the toughening agent, but also has good compatibility with polyvinyl chloride. After forming composite particles, coextrusion and kneading with the toughening agent to make a composite material with excellent strength, toughness and cold resistance.

Benefits of technology

It achieves good compatibility between modified polyester and polyvinyl chloride, improves the strength, toughness and cold resistance of the composite material, and is suitable for the sole material of shoes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570206A_ABST
    Figure CN119570206A_ABST
Patent Text Reader

Abstract

The invention relates to a modified copolyester material, and discloses modified polyester as well as a preparation method and application thereof. The melting point of the modified polyester is less than or equal to 130 DEG C, the modified polyester and the polyvinyl chloride are subjected to melt mixing according to the weight ratio of 1: (0.5-2) to form composite particles, then the composite particles and the flexibilizer are subjected to co-extrusion mixing according to the weight ratio of 1: (0.1-0.15) to prepare the composite board with the thickness of 1-2 cm, and the impact resistance of the composite board is 390 kg / mm or above. The preparation method of the modified polyester comprises the following steps: under an esterification reaction condition, mixing a modified monomer, a binary acid monomer, a dihydric alcohol monomer and a catalyst, and then carrying out a first-stage reaction; a second-stage reaction is carried out under the polycondensation reaction condition, the modified monomer contains polyhydric alcohol with the structure shown in the formula (I) and a monomer with the structure shown in the formula (II), and the molar ratio of the monomer with the structure shown in the formula (II) to the binary acid monomer is (0.4-1.5): 1. The modified polyester is low in melting point and good in compatibility with polyvinyl chloride, and the composite material formed by melting and mixing the modified polyester and the polyvinyl chloride has excellent strength, toughness and cold resistance. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified copolyester material, in particular to a modified polyester and a preparation method and application thereof. Background Art

[0002] The sole materials of shoes are mainly polyvinyl chloride (PVC), polyethylene, polyethylene copolymer, polycaprolactone, 1,4-cyclohexanedimethanol (CHDM) modified polyester PETG, etc. These materials are mixed with impact performance improvers and processed into thick plates for shoes. The impact performance improvers mainly include epoxy-containing ethylene copolymers, anhydride-grafted ethylene copolymers (such as maleic anhydride copolymers), and more commonly used is polybutylene adipate. Among these substrates, polyvinyl chloride, polyethylene, and polyethylene copolymer materials are relatively low in price, but the use effect is average; while polycaprolactone and PETG are expensive.

[0003] Polyethylene terephthalate and polybutylene terephthalate have excellent mechanical properties and heat resistance, but poor impact resistance, especially at low temperatures below 0°C. Due to the high melting point, this saturated polyester needs to be mixed with the impact modifier at a higher temperature (>280°C). At this time, the impact modifier has poor temperature resistance and is severely degraded. Therefore, conventional polyester cannot be directly mixed with the impact modifier, and low melting point polyester must be used. At present, the method for preparing low melting point polyester is to add some special copolymerization modification monomers, which mainly include isophthalic acid, 2-methyl-1,3-propanediol, 2,2-methyl-1,3-propanediol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 1,4-cyclohexanedimethanol (CHDM); for example, the isophthalic acid modified copolyester substrate used in CN1491987A uses isophthalic acid as the modification monomer; CN108467479A uses furan dicarboxylic acid as the modification monomer of polyester; EP2411471A1 and CN104411766A both use 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 1,4-cyclohexanedimethanol as the modification monomers of polyester.

[0004] Although the modified monomers mentioned above can be used to synthesize low-melting polyesters, these low-melting polyesters have poor compatibility with polyvinyl chloride (PVC), and the boards obtained by mixing the two have poor toughness and unsatisfactory impact resistance. In addition, the prices of modified monomers such as 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 1,4-cyclohexanedimethanol are relatively expensive. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems in the prior art that low melting point polyester has poor compatibility with polyvinyl chloride and the strength and toughness of the mixed plate are poor, and to provide a modified polyester and a preparation method and application thereof.

[0006] The inventors of the present invention have found in their research that a low-melting-point modified polyester can be synthesized by using a specific modified monomer as a comonomer of polyester. The modified polyester not only has a low melting point and can be effectively mixed with a toughening agent to avoid degradation of the toughening agent, but also has good compatibility with polyvinyl chloride. The composite particles obtained by melt-mixing the two are further co-extruded and mixed with a toughening agent to form a composite material, which has excellent strength, toughness and cold resistance and is suitable for producing shoe sole materials.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a modified polyester, wherein the melting point of the modified polyester is less than or equal to 130°C, the modified polyester is melt-mixed with polyvinyl chloride at a weight ratio of 1:0.5-2 to form composite particles, and then co-extruded and mixed with a toughening agent at a weight ratio of 1:0.1-0.15 to form a composite board with a thickness of 1-2 cm, and the impact resistance of the composite board is above 390kg / mm.

[0008] A second aspect of the present invention provides a method for preparing a modified polyester, comprising the following steps:

[0009] (1) Under esterification reaction conditions, a modified monomer, a dibasic acid monomer, a diol monomer and a catalyst are mixed and then subjected to a first stage reaction to obtain a prepolymer;

[0010] (2) subjecting the prepolymer to a second stage reaction under polycondensation reaction conditions;

[0011] The modified monomer contains a polyol having a structure represented by formula (I) and a monomer having a structure represented by formula (II).

[0012] Among them, R I and R II Each is independently hydrogen or C1-C4 alkyl, preferably hydrogen or methyl, and n is a positive integer of 4-11; R1, R2, R3 and R4 are each independently hydrogen or C1-C4 alkyl, preferably hydrogen or methyl, more preferably hydrogen; the molar amount of the monomer having the structure represented by formula (II) accounts for 30-60% of the total molar amount of the monomer and the dibasic acid monomer.

[0013] The third aspect of the present invention provides the use of the modified polyester and / or the modified polyester prepared by the above method in a shoe sole material.

[0014] A fourth aspect of the present invention provides a method for preparing a composite material, the method comprising the following steps:

[0015] S1, mixing the modified polyester and / or the modified polyester obtained by the above method with polyvinyl chloride and an additive, and then melt-kneading to obtain composite particles;

[0016] S2, mixing the composite particles with a toughening agent and performing co-extrusion kneading.

[0017] The modified polyester provided by the present invention not only has a low melting point and can be effectively mixed with a toughening agent to avoid degradation of the toughening agent, but also has good compatibility with polyvinyl chloride. The composite particles obtained by melt-mixing the two are further co-extruded and mixed with a toughening agent to form a composite material, which has excellent strength, toughness and cold resistance and is suitable for producing sole materials for shoes.

[0018] The preparation method provided by the present invention directly mixes multiple monomers and then performs esterification reaction and polycondensation reaction to obtain modified polyester, which has simple operation, strong process controllability and is suitable for industrial production. DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] The first aspect of the present invention provides a modified polyester, wherein the melting point of the modified polyester is lower than or equal to 130°C, the modified polyester is melt-kneaded with polyvinyl chloride at a weight ratio of 1:0.5-2 to form composite particles, and then co-extruded and kneaded with a toughening agent at a weight ratio of 1:0.1-0.15 to form a composite plate with a thickness of 1-2 cm, and the impact resistance of the composite plate is above 390 kg / mm.

[0021] In the present invention, the melting point is tested and characterized according to 5.3.1 Method A (microscope method) in GB / T 14190-2008 "Test Method for Fiber-Grade Polyester Chips (PET)".

[0022] In the present invention, when the modified polyester provided by the present invention is used to prepare the composite board for performance testing, a twin-screw extruder is used for preparation. The specific method is: the modified polyester provided by the present invention is mixed with polyvinyl chloride and an optional auxiliary agent in a twin-screw extruder (the weight ratio of the modified polyester to polyvinyl chloride is 1:0.5-2), the temperature is raised to 90-110°C, and the mixture is kept warm for 25-35 minutes to obtain a mixture, and then the mixture is plasticized and melt-extruded in a twin-screw extruder. The main engine speed of the extruder is 150-250r / min, the pressure is 10-15MPa, and the operating temperature is: from the feed port to the die head, the temperature of the first zone is 100-120°C, the temperature of the second zone is 130-140°C, the temperature of the third zone is 140-150°C, and the temperature of the fourth zone is 150-160°C. After extrusion, drawing, and cooling, The composite particles are obtained by pelletizing and drying; the composite particles and the toughening agent are co-extruded and mixed in a screw at a weight ratio of 1:0.1-0.15 to extrude into a composite plate with a thickness of 1-2 cm; the auxiliary agents are zinc oxide, epoxy resin, triethyl phosphate, dibutyl tin dilaurate and dioctyl phthalate, and the toughening agent is selected from at least one of polybutylene succinate, polyethylene succinate, polycaprolactone and polybutylene adipate; the weight ratio of the modified polyester, polyvinyl chloride, zinc oxide, epoxy resin, triethyl phosphate, dibutyl tin dilaurate, dioctyl phthalate and toughening agent is 1:0.8-1.2:0.01-0.05:0.02-0.08:0.02-0.08:0.01-0.05:0.02-0.08:0.2-0.3.

[0023] In the present invention, the impact resistance test of the composite sheet is tested according to the method in "ASTM-D3763 Standard Test Method for High-Speed ​​Puncture Performance of Plastics Using Load and Displacement Sensors", and 10 samples are also tested in each batch. Preferably, the impact resistance of the composite sheet is 400kg / mm ​​or more, more preferably 410kg / mm ​​or more. The modified polyester provided by the present invention has a low melting point and can form good compatibility with polyvinyl chloride. It can not only be effectively mixed with a toughening agent to avoid degradation of the toughening agent, but also the material formed by mixing with polyvinyl chloride (PVC) and a toughening agent has excellent strength, toughness and cold resistance, strong impact resistance, good tortuosity, and can be effectively applied to the production of sole materials.

[0024] According to the present invention, preferably, the melting point of the modified polyester is less than or equal to 120° C., and more preferably, the melting point of the modified polyester is 100° C.-120° C. Based on the low melting point of the modified polyester in the present application, it can be mixed with the toughening agent at a lower temperature to reduce or avoid the degradation of the toughening agent at high temperature, which is beneficial to improving the impact resistance of the modified polyester.

[0025] According to the present invention, preferably, the glass transition temperature of the modified polyester is 60-70°C, the intrinsic viscosity is 0.7-0.85 dL / g, and the terminal carboxyl content is 20-35 mol / t. The modified polyester has a low melting point, good compatibility with polyvinyl chloride, and a certain degree of improvement in the glass transition temperature, so that the modified polyester has good processing performance.

[0026] In the present invention, the glass transition temperature of the modified polyester is calculated according to the differential scanning calorimetry (DSC) test, the intrinsic viscosity is tested according to the 5.1 method in the "GB / T14190-2017 Test Method for Fiber-Grade Polyester Chips", and the terminal carboxyl group is tested according to the 5.4 method in the "GB / T14190-2017 Test Method for Fiber-Grade Polyester Chips". Among them, the process of calculating the glass transition temperature by differential scanning calorimetry (DSC) test includes: under nitrogen protection, using DSC thermal analysis to increase the temperature from 25°C to 290°C at a heating rate of 10°C / min, hold for 5 minutes, then cool down to 25°C at a rate of 400°C / min, then increase the temperature from 25°C to 290°C at a heating rate of 10°C / min, hold for 5 minutes, and finally cool down to 100°C at a rate of 10°C / min, and calculate the glass transition temperature Tg according to the second heating curve.

[0027] According to the present invention, preferably, the modified polyester contains a structural unit A represented by formula (I),

[0028] Among them, R I and R II Each is independently hydrogen or C1-C4 alkyl, preferably hydrogen or methyl, and n is a positive integer from 4 to 11. The inventors found that under this preferred embodiment, the modified polyester contains a large number of side-positioned -OH groups, and the side-positioned polar -OH groups form certain polar interactions with the polar side-positioned -Cl groups in polyvinyl chloride, so that the modified polyester has good compatibility with polyvinyl chloride (PVC).

[0029] According to the present invention, the structural unit A can be obtained by infrared and nuclear magnetic detection analysis. Preferably, the content of the structural unit A represented by formula (I) in the modified polyester is less than or equal to 1% by weight, more preferably 0.1-1% by weight. The inventors have found that under this preferred embodiment, the compatibility of the modified polyester with polyvinyl chloride is better.

[0030] According to the present invention, preferably, the modified polyester further contains a structural unit B represented by formula (II) and a structural unit C represented by formula (III),

[0031]

[0032] Wherein, R1, R2, R3, R4, R5, R6, R7 and R8 are each independently hydrogen or C1-C4 alkyl, for example, hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl; preferably hydrogen or methyl, more preferably hydrogen. The inventors found that under this preferred embodiment, structural unit A and structural unit B can cooperate with each other to reduce the melting point of the modified polyester and improve the compatibility of the modified polyester with polyvinyl chloride, so that the sole material made using the modified polyester as a raw material has good strength and toughness, and good folding and bending test results.

[0033] According to the present invention, preferably, the molar amount of the structural unit B accounts for 30-60% of the total molar amount of the structural unit B and the structural unit C. The molar amounts of the structural unit B and the structural unit C can be measured by gas chromatography, respectively. The inventors have found that under this preferred embodiment, it is beneficial to further reduce the melting point of the modified polyester and reduce the raw material cost of the polyester modification.

[0034] According to the present invention, preferably, the modified polyester further contains antimony or titanium. More preferably, the content of antimony or titanium in the modified polyester is less than or equal to 0.05 wt%, more preferably less than or equal to 0.03 wt%.

[0035] A second aspect of the present invention provides a method for preparing a modified polyester, comprising the following steps:

[0036] (1) Under esterification reaction conditions, a modified monomer, a dibasic acid monomer, a diol monomer and a catalyst are mixed and then subjected to a first stage reaction to obtain a prepolymer;

[0037] (2) subjecting the prepolymer to a second stage reaction under polycondensation reaction conditions;

[0038] The modified monomer contains a polyol having a structure represented by formula (I) and a monomer having a structure represented by formula (II).

[0039]

[0040] Among them, R I and R II Each is independently hydrogen or C1-C4 alkyl, preferably hydrogen or methyl, and n is a positive integer of 4-11; R1, R2, R3 and R4 are each independently hydrogen or C1-C4 alkyl, preferably hydrogen or methyl, more preferably hydrogen;

[0041] The molar amount of the monomer having the structure represented by formula (II) accounts for 30-60% of the total molar amount of the monomer and the dibasic acid monomer.

[0042] The inventors have discovered that under the action of two modifying monomers, a polyol having a structure represented by formula (I) and a monomer having a structure represented by formula (II), mutually cooperative structural units A and structural units B can be formed in the modified polyester, thereby effectively reducing the melting point of the modified polyester and improving the compatibility of the modified polyester with polyvinyl chloride (PVC).

[0043] As a specific embodiment of the present invention, the structural formula of the polyol is as shown in formula (IV), m is a positive integer of 3 to 10. The polyol represented by formula (IV) is a linear condensate of resorcinol and formaldehyde, and can be prepared by condensation reaction using resorcinol and formaldehyde as substrates. The inventors have found that under this preferred embodiment, the polyol as a modifying monomer can form a better modification effect on polyester, and a modified polyester with good compatibility with PVC is obtained.

[0044] According to the present invention, preferably, the monomer having the structure represented by formula (II) is isophthalic acid, which has low price and good modification effect on polyester copolymer.

[0045] In the present invention, the dibasic acid monomer may be any dibasic acid that can be used to prepare polyester. Preferably, the dibasic acid monomer is an acid or ester having a structure represented by formula (III). R5, R6, R7 and R8 are each independently hydrogen or C1-C4 alkyl, preferably hydrogen or methyl, more preferably hydrogen. Exemplarily, the dibasic acid monomer can be terephthalic acid, dimethyl terephthalate, diethyl terephthalate, dipropyl terephthalate, etc. The inventors found that under this preferred embodiment, the modified polyester contains the structural unit B shown in formula (II) and the structural unit C shown in formula (III), so that the polyester is more compatible with PVC, and thus the impact resistance of the composite board is better.

[0046] In the present invention, the diol monomer may be any diol that can be used to prepare polyester, preferably an aliphatic diol, such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,3-butanediol, etc., more preferably ethylene glycol.

[0047] According to the present invention, preferably, the catalyst is an antimony-containing catalyst or a titanium-containing catalyst, more preferably selected from antimony glycol, antimony acetate, antimony trioxide, titanium glycol, nano titanium dioxide or tetrabutyl titanate; the amount of the catalyst used can be the same as that of conventional polyester. For example, based on 100 parts by weight of the dibasic acid monomer, the amount of the catalyst used is 0.05-0.2 parts by weight.

[0048] In the present invention, the above-mentioned polyol, monomer having the structure represented by formula (II), dibasic acid monomer, diol monomer and catalyst can be obtained commercially or prepared by the preparation method disclosed in the prior art.

[0049] According to the present invention, preferably, based on the total amount of the modified monomer, the dibasic acid monomer, the diol monomer and the catalyst, the amount of the polyol is less than or equal to 1% by weight, more preferably 0.1-1% by weight. In this preferred embodiment, the molar amount of the monomer having the structure shown in formula (II) accounts for 30-60% of the total molar amount of the monomer and the dibasic acid monomer, and the weight of the polyol accounts for less than 1% of the total weight of all substrates, which is conducive to reducing the melting point of the modified polyester and further improving the compatibility with PVC.

[0050] In the present invention, the end condition of the first stage reaction can be determined by the test personnel according to the actual situation, preferably, it can be determined according to the water output of the product reaching the theoretical value. After the first stage reaction, it is necessary to release the pressure to normal pressure, gradually increase the temperature and transfer to the low vacuum stage for the second stage reaction. The end condition of the second stage reaction can also be determined by the test personnel according to the actual situation, preferably, it can be determined according to the stirring power reaching the rated value.

[0051] According to the present invention, preferably, in step (1), the esterification reaction conditions at least include: isolation of oxygen, a temperature of 200-260°C, and a pressure of 2.2-2.8MPa. The inventors have found that under this preferred embodiment, polyols, monomers having a structure shown in formula (II), diol monomers, and dibasic acid monomers have better esterification effects, thereby enabling the subsequently obtained modified polyester to have higher processing properties. Isolation of oxygen is usually achieved by filling the reaction system with an inert gas such as nitrogen or helium. The first stage reaction is carried out under stirring, and the stirring rate can be determined by the experimenter according to actual conditions.

[0052] According to the present invention, preferably, in step (2), the polycondensation reaction conditions at least include: a temperature of 270-290° C. and a pressure of less than 100 Pa. The inventors have found that under this preferred embodiment, the prepolymer can have a better polycondensation effect, thereby improving the modification effect of the polyol and the monomer having the structure shown in formula (II) on the polyester.

[0053] According to a particularly preferred embodiment of the present invention, the method for preparing the modified polyester comprises the following steps:

[0054] (1) In the absence of oxygen, a polyol represented by formula (IV), isophthalic acid, a dibasic acid, an aliphatic diol and an antimony-containing catalyst are mixed, and a first-stage reaction is carried out at a temperature of 200-260° C. and a pressure of 2.2-2.8 MPa until the water output reaches a theoretical value, thereby obtaining a prepolymer;

[0055] Where m is a positive integer between 3 and 10;

[0056] (2) The first stage reaction system is vented to normal pressure, and the temperature is gradually raised to enter the low vacuum stage. After the low vacuum time is about 45 minutes, the prepolymer is subjected to the second stage reaction at a temperature of 270-290° C. and a pressure of less than 100 Pa until the stirring power reaches the rated value and the material is discharged.

[0057] The modified polyester provided by the present invention is mixed with polyvinyl chloride to form composite particles, which are further mixed with a toughening agent to form a plate, which has excellent toughness, cold resistance and strength, and has excellent results in various performance tests. Based on this, the third aspect of the present invention provides the use of the modified polyester and / or the modified polyester prepared by the method in the sole material.

[0058] A fourth aspect of the present invention provides a method for preparing a composite material, the method comprising the following steps:

[0059] S1, mixing the modified polyester and / or the modified polyester obtained by the above method with polyvinyl chloride and an additive, and then melt-kneading to obtain composite particles;

[0060] S2, mixing the composite particles with a toughening agent and performing co-extrusion kneading.

[0061] In the present invention, the auxiliary agent can improve the mixing effect of the modified polyester and polyvinyl chloride, and preferably, the auxiliary agent contains zinc oxide, epoxy resin, triethyl phosphate, dibutyltin dilaurate and dioctyl phthalate. The toughening agent can improve the impact resistance of the composite material, and preferably, the toughening agent is selected from at least one of polybutylene succinate, polyethylene succinate, polycaprolactone and polybutylene adipate, and more preferably polybutylene succinate.

[0062] According to the present invention, preferably, the modified polyester and polyvinyl chloride are mixed in a weight ratio of 1:0.5-2, and additives such as zinc oxide, epoxy resin, triethyl phosphate, dibutyltin dilaurate, and dioctyl phthalate are added, and melt mixing is performed to obtain composite particles. The inventors have found that under this preferred embodiment, it is beneficial to improve the strength and toughness of the composite material, and it better meets the performance requirements of the sole material.

[0063] According to the present invention, illustratively, the weight ratio of modified polyester, polyvinyl chloride, zinc oxide, epoxy resin, triethyl phosphate, dibutyltin dilaurate, dioctyl phthalate and toughening agent is 1:0.8-1.2:0.01-0.05:0.02-0.08:0.02-0.08:0.01-0.05:0.02-0.08:0.2-0.3.

[0064] In the present invention, the melt mixing process of the modified polyester, polyvinyl chloride and the auxiliary agent and the co-extrusion mixing process of the composite particles and the toughening agent can be carried out using conventional equipment, for example, a twin-screw extruder. For example, the modified polyester is mixed with polyvinyl chloride and the auxiliary agent and then heated to 90-110°C, kept warm for 25-35 minutes to obtain a mixture, and then the mixture is plasticized and melt-extruded in a twin-screw extruder to obtain composite particles. At this time, the main engine speed of the extruder is 150-250r / min, the pressure is 10-15MPa, and the operating temperature is: from the feed port to the die head, the temperature of the first zone is 100-120°C, the temperature of the second zone is 130-140°C, the temperature of the third zone is 140-150°C, and the temperature of the fourth zone is 150-160°C. After extrusion, drawing, cooling, pelletizing, and drying, composite particles are obtained. Further, the composite particles and the toughening agent are co-extruded and mixed in the screw to extrude the composite material. The thickness of the composite material (sheet) can be greater than or equal to 1cm.

[0065] The plate produced by the above method has excellent toughness, cold resistance and strength, and the results of various performance tests are excellent, and is suitable for the production of soles.

[0066] The present invention will be described in detail below through examples.

[0067] In the following embodiments, the detection methods of various parameters and performances are as follows:

[0068] (1) Folding test: The sample size is 20×20 cm. Fold it in half horizontally and vertically to check whether it is broken. Repeat the test 10 times for 10 samples. If one of them is broken, it is considered unqualified.

[0069] (2) Impact resistance test: The test is carried out according to the method in "ASTM-D3763 Standard Test Method for High-Speed ​​Puncture Performance of Plastics Using Load and Displacement Sensors". Similarly, each batch of 10 samples has an average value of less than 250kg / mm, which is considered unqualified.

[0070] (3) ROSS room temperature flexure (23°C) and cold flexure (-10°C) tests: The test is conducted in accordance with the method in ASTM-D1052 Ross flexure test. The maximum number of room temperature flexure tests is 75,000 times, and the maximum number of cold flexure tests is 25,000 times. The center cut of the sample is considered unqualified if there is a crack exceeding 0.5 inches or a break.

[0071] (4) Melting point was tested according to 5.3.1 Method A (microscope method) in GB / T 14190-2008 Test Method for Fiber Grade Polyester Chips (PET).

[0072] (5) The glass transition temperature was calculated by differential scanning calorimetry (DSC). The specific process was as follows: under nitrogen protection, DSC thermal analysis was used to increase the temperature from 25°C to 290°C at a heating rate of 10°C / min, hold for 5 min, then cool to 25°C at a rate of 400°C / min, then increase the temperature from 25°C to 290°C at a heating rate of 10°C / min, hold for 5 min, and finally cool to 100°C at a rate of 10°C / min. The glass transition temperature Tg was calculated based on the second heating curve.

[0073] (6) The intrinsic viscosity was tested according to method 5.1 of GB / T14190-2017 Test method for fiber-grade polyester chips.

[0074] (7) The terminal carboxyl group is tested according to method 5.4 in GB / T14190-2017 Test method for fiber-grade polyester chips.

[0075] In the following examples, unless otherwise specified, the raw materials and reagents used are conventional commercially available products; normal pressure refers to a gauge pressure of 0.

[0076] Example 1

[0077] In a 20L reactor, 3.5kg of terephthalic acid (PAT), 1.5kg of isophthalic acid, 3kg of ethylene glycol, 11g of the polyol represented by formula (V), and 3g of ethylene glycol antimony were added.

[0078]

[0079] The esterification is carried out at a temperature of 230°C and a pressure (gauge pressure) of 2.5 MPa. When the water output reaches the theoretical value, the esterification is terminated, the pressure is released to normal pressure, and stirring is continued for 10 minutes. The temperature is gradually increased to enter the low vacuum stage. After the low vacuum time is about 45 minutes, the high vacuum polycondensation stage (pressure <100 Pa) is entered. The polycondensation is carried out at a temperature of 280°C. When the stirring power reaches the rated value, the material is discharged to obtain modified polyester.

[0080] Example 2

[0081] In a 20L reactor, 3kg of terephthalic acid (PAT), 2kg of isophthalic acid, 3kg of ethylene glycol, 57g of the polyol represented by formula (V), and 3g of antimony trioxide were added;

[0082] The esterification is carried out at a temperature of 230°C and a pressure (gauge pressure) of 2.5 MPa. When the water output reaches the theoretical value, the esterification is terminated, the pressure is released to normal pressure, and stirring is continued for 10 minutes. The temperature is gradually increased to enter the low vacuum stage. After the low vacuum time is about 45 minutes, the high vacuum polycondensation stage (pressure <100 Pa) is entered. The polycondensation is carried out at a temperature of 280°C. When the stirring power reaches the rated value, the material is discharged to obtain modified polyester.

[0083] Example 3

[0084] In a 20L reactor, 2kg of terephthalic acid (PAT), 3kg of isophthalic acid, 3kg of ethylene glycol, 47g of the polyol represented by formula (V), a linear condensate of resorcinol and formaldehyde (A), and 3g of ethylene glycol antimony were added;

[0085] The esterification is carried out at a temperature of 230°C and a pressure (gauge pressure) of 2.5 MPa. When the water output reaches the theoretical value, the esterification is terminated, the pressure is released to normal pressure, and stirring is continued for 10 minutes. The temperature is gradually increased to enter the low vacuum stage. After the low vacuum time is about 45 minutes, the high vacuum polycondensation stage (pressure <100 Pa) is entered. The polycondensation is carried out at a temperature of 280°C. When the stirring power reaches the rated value, the material is discharged to obtain modified polyester.

[0086] Example 4

[0087] In a 20L reactor, 2.5kg of terephthalic acid (PAT), 2.5kg of isophthalic acid, 3kg of ethylene glycol, 35g of the polyol represented by formula (VI), and 3g of ethylene glycol antimony were added.

[0088]

[0089] The esterification is carried out at a temperature of 220°C and a pressure (gauge pressure) of 2.6 MPa. When the water output reaches the theoretical value, the esterification is terminated, the pressure is released to normal pressure, and stirring is continued for 10 minutes. The temperature is gradually increased to enter the low vacuum stage. After the low vacuum time is about 45 minutes, the high vacuum polycondensation stage (pressure <100 Pa) is entered. The polycondensation is carried out at a temperature of 270°C. When the stirring power reaches the rated value, the material is discharged to obtain modified polyester.

[0090] Example 5

[0091] In a 20L reactor, 2.7kg of terephthalic acid (PAT), 2.3kg of isophthalic acid, 3kg of ethylene glycol, 25g of the polyol represented by formula (VII), and 3g of ethylene glycol antimony were added.

[0092]

[0093] The esterification was carried out at a temperature of 260°C and a pressure (gauge pressure) of 2.1 MPa. When the water output reached the theoretical value, the esterification was terminated, the pressure was released to normal pressure, and stirring was continued for 10 minutes. The temperature was gradually increased to enter the low vacuum stage. After the low vacuum time was about 45 minutes, the high vacuum polycondensation stage (pressure <100 Pa) was entered. The polycondensation was carried out at a temperature of 290°C. When the stirring power reached the rated value, the material was discharged to obtain modified polyester.

[0094] Example 6

[0095] The modified polyester was prepared according to the method of Example 3, except that the amount of the polyol represented by formula (V) was replaced with 100 g.

[0096] Example 7

[0097] The modified polyester was prepared according to the method of Example 3, except that the amount of antimony ethylene glycol was replaced by 15 g.

[0098] Example 8

[0099] The modified polyester was prepared according to the method of Example 3, except that antimony ethylene glycol was replaced by tetrabutyl titanate.

[0100] Example 9

[0101] The modified polyester was prepared according to the method of Example 3, except that the polyol represented by formula (V) was replaced by the polyol represented by formula (VIII).

[0102]

[0103] Comparative Example 1

[0104] In a 20L reactor, 2.5kg of terephthalic acid (PAT), 2.5kg of isophthalic acid, 3kg of ethylene glycol and 3g of ethylene glycol antimony were added, and esterification was carried out at a temperature of 220°C and a pressure (gauge pressure) of 2.6MPa. When the water output reached the theoretical value, the esterification was terminated, the pressure was released to normal pressure, and stirring was continued for 10min. The temperature was gradually increased to enter the low vacuum stage. After the low vacuum time was about 45min, the high vacuum polycondensation stage (pressure <100Pa) was entered, and polycondensation was carried out at a temperature of 270°C. When the stirring power reached the rated value, the material was discharged to obtain modified polyester.

[0105] Comparative Example 2

[0106] In a 20L reactor, 4.4kg of terephthalic acid (PAT), 0.6kg of isophthalic acid, 3kg of ethylene glycol, 47g of the polyol represented by formula (V), and 3g of ethylene glycol antimony were added;

[0107] The esterification is carried out at a temperature of 230°C and a pressure (gauge pressure) of 2.5 MPa. When the water output reaches the theoretical value, the esterification is terminated, the pressure is released to normal pressure, and stirring is continued for 10 minutes. The temperature is gradually increased to enter the low vacuum stage. After the low vacuum time is about 45 minutes, the high vacuum polycondensation stage (pressure <100 Pa) is entered. The polycondensation is carried out at a temperature of 280°C. When the stirring power reaches the rated value, the material is discharged to obtain modified polyester.

[0108] Comparative Example 3

[0109] In a 20L reactor, 5kg of terephthalic acid (PAT), 3kg of ethylene glycol, 47g of the polyol represented by formula (V), and 3g of ethylene glycol antimony were added;

[0110] The esterification is carried out at a temperature of 230°C and a pressure (gauge pressure) of 2.5 MPa. When the water output reaches the theoretical value, the esterification is terminated, the pressure is released to normal pressure, and stirring is continued for 10 minutes. The temperature is gradually increased to enter the low vacuum stage. After the low vacuum time is about 45 minutes, the high vacuum polycondensation stage (pressure <100 Pa) is entered. The polycondensation is carried out at a temperature of 280°C. When the stirring power reaches the rated value, the material is discharged to obtain modified polyester.

[0111] Test Example 1

[0112] The contents of the structural unit A of the corresponding formula (I), the molar amount of the structural unit B of the corresponding formula (II), the molar amount of the structural unit C of the corresponding formula (III) and the metal element content in the modified polyesters prepared in Test Examples 1 to 9 and Comparative Examples 1 to 3 are shown in Table 1; the structural unit A is obtained by infrared and nuclear magnetic resonance detection and analysis, and the molar amounts of the structural unit B and the structural unit C are respectively measured by gas chromatography.

[0113] Table 1

[0114]

[0115] Test Example 2

[0116] The melting point, glass transition temperature, intrinsic viscosity and terminal carboxyl group of the modified polyesters prepared in Example 1 to Example 9 and Comparative Example 1 to Comparative Example 3 were tested. The results are shown in Table 2.

[0117] Table 2

[0118] serial number Melting point, °C Glass transition temperature, °C Intrinsic viscosity, dL / g Terminal carboxyl content, mol / t Example 1 125.6 65.2 0.762 28 Example 2 120.2 63.3 0.782 23.6 Example 3 110.7 60.5 0.795 33 Example 4 116.5 62.3 0.765 28 Example 5 118.2 62.0 0.776 24.6 Example 6 107.9 61.2 0.789 33.8 Example 7 110.6 60.4 0.793 34.5 Example 8 110.5 60.4 0.797 20.6 Example 9 110.3 60.8 0.789 32 Comparative Example 1 118.7 60.0 0.785 25 Comparative Example 2 225.0 70.3 0.753 22.4 Comparative Example 3 253.9 78.2 0.745 22.8

[0119] Test Example 3

[0120] The modified polyesters obtained in Examples 1 to 9 and Comparative Examples 1 to 3 were mixed with polyvinyl chloride to prepare a composite sheet for a sole material. The specific method was as follows: 5 kg of the modified polyester was mixed with 5 kg of polyvinyl chloride (PVC), 0.1 kg of zinc oxide, 0.2 kg of epoxy resin, 0.2 kg of triethyl phosphate, 0.1 kg of dibutyltin dilaurate, and 0.2 kg of dioctyl phthalate, and then the mixture was heated to 100° C. and kept warm for 30 minutes to obtain a mixture; the mixture was added The materials are melted and extruded in a twin-screw extruder. The main engine speed of the extruder is 200r / min, the pressure is 12MPa, and the operating temperature is: from the feeding port to the die head, the temperature of zone 1 is 110°C, the temperature of zone 2 is 135°C, the temperature of zone 3 is 145°C, and the temperature of zone 4 is 155°C. After extrusion, drawing, cooling, pelletizing and drying, composite particles are obtained. The dried composite particles are co-extruded and mixed with 1.2kg of toughening agent polybutylene adipate in a screw to form a composite plate with a thickness of 1.5cm.

[0121] The composite panels corresponding to Examples 1 to 9 and Comparative Examples 1 to 3 were subjected to folding resistance test, impact resistance test, ROSS room temperature flexure (23°C) and cold resistance flexure (-10°C) tests, and the results are shown in Table 3.

[0122] Table 3

[0123]

[0124] The modified polyester provided by the present invention has a low melting point, which can be reduced to about 110° C., and the composite board prepared by blending with PVC has excellent toughness and impact resistance, and can be applied to the production of shoe materials.

[0125] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A modified polyester, characterized in that: The melting point of the modified polyester is less than or equal to 130°C. The modified polyester is melt-mixed with polyvinyl chloride at a weight ratio of 1:0.5-2 to form composite particles, and then co-extruded and mixed with a toughening agent at a weight ratio of 1:0.1-0.15 to form a composite plate with a thickness of 1-2 cm. The impact resistance of the composite plate is above 390 kg / mm.

2. The modified polyester according to claim 1, characterized in that The melting point of the modified polyester is less than or equal to 120°C; Preferably, the modified polyester has a glass transition temperature of 60-70° C., an intrinsic viscosity of 0.7-0.85 dL / g, and a terminal carboxyl content of 20-35 mol / t.

3. The modified polyester according to claim 1 or 2, characterized in that The modified polyester contains a structural unit A represented by formula (I), Among them, R I and R II Each is independently hydrogen or C1-C4 alkyl, preferably hydrogen or methyl, and n is a positive integer of 4-11; Preferably, the content of the structural unit A represented by formula (I) in the modified polyester is less than or equal to 1% by weight, more preferably 0.1-1% by weight.

4. The modified polyester according to claim 1 or 2, characterized in that The modified polyester contains a structural unit B represented by formula (II) and a structural unit C represented by formula (III), wherein R1, R2, R3, R4, R5, R6, R7 and R8 are each independently hydrogen or C1-C4 alkyl, preferably hydrogen or methyl, more preferably hydrogen; Preferably, the molar amount of the structural unit B accounts for 30-60% of the total molar amount of the structural unit B and the structural unit C.

5. The modified polyester according to claim 1 or 2, characterized in that: The modified polyester contains antimony or titanium; Preferably, the content of antimony or titanium in the modified polyester is less than or equal to 0.05 wt %, more preferably less than or equal to 0.03 wt %.

6. A method for preparing modified polyester, characterized in that: The following steps are involved: (1) Under esterification reaction conditions, a modified monomer, a dibasic acid monomer, a diol monomer and a catalyst are mixed and then subjected to a first stage reaction to obtain a prepolymer; (2) subjecting the prepolymer to a second stage reaction under polycondensation reaction conditions; The modified monomer contains a polyol having a structure represented by formula (I) and a monomer having a structure represented by formula (II). Among them, R I and R II Each is independently hydrogen or C1-C4 alkyl, preferably hydrogen or methyl, and n is a positive integer of 4-11; R1, R2, R3 and R4 are each independently hydrogen or C1-C4 alkyl, preferably hydrogen or methyl, more preferably hydrogen; The molar amount of the monomer having the structure represented by formula (II) accounts for 30-60% of the total molar amount of the monomer and the dibasic acid monomer.

7. The preparation method according to claim 6, characterized in that: The diol monomer is an aliphatic diol, and the dibasic acid monomer is an acid or ester having a structure represented by formula (III). R5, R6, R7 and R8 are each independently hydrogen or C1-C4 alkyl, preferably hydrogen or methyl, more preferably hydrogen; Preferably, the catalyst is an antimony-containing catalyst or a titanium-containing catalyst, more preferably selected from antimony glycolate, antimony acetate, antimony trioxide, titanium glycolate, nano titanium dioxide or tetrabutyl titanate; Preferably, based on the total amount of the modified monomer, the dibasic acid monomer, the diol monomer and the catalyst, the amount of the polyol is less than or equal to 1 wt %.

8. The preparation method according to claim 6 or 7, characterized in that: In step (1), the esterification reaction conditions at least include: isolation of oxygen, temperature of 200-260° C., and pressure of 2.2-2.8 MPa; Preferably, in step (2), the polycondensation reaction conditions at least include: a temperature of 270-290° C. and a pressure of less than 100 Pa.

9. Use of the modified polyester according to any one of claims 1 to 5 and / or the modified polyester prepared by the method according to any one of claims 6 to 8 in shoe sole materials.

10. A method for preparing a composite material, characterized in that: The method comprises the following steps: S1. Mixing the modified polyester according to any one of claims 1 to 5 and / or the modified polyester obtained by the method according to any one of claims 6 to 8 with polyvinyl chloride and an additive, and then melt-kneading to obtain composite particles; S2, mixing the composite particles with a toughening agent for co-extrusion and kneading; The auxiliary agent contains zinc oxide, epoxy resin, triethyl phosphate, dibutyltin dilaurate and dioctyl phthalate; The toughening agent is selected from at least one of polybutylene succinate, polyethylene succinate, polycaprolactone and polybutylene adipate.

Citation Information

Patent Citations

  • Ternary blends of terephthalate or isophthalate polyesters containing eg, chdm, and tmcd

    CN104411766A

  • Toughening 2,5-furan dioctyl phthalate copolyester and preparation method thereof

    CN108467479A

  • Low temperature workable modified toughness increasing polyester material

    CN1491987A

  • Polyester blends

    EP2411471A1

  • Environment-friendly regeneration method of PVC pipe

    CN112321967A